Microwave assisted treatment of carpentry waste wood flour with natural deep eutectic solvents for nanocellulose production and removal of organic pollutants - Giovanni Cisternino; Francesca Baldassarre; Giuseppe Ciccarella; Piero Mastrorilli; Maria Michela Dell'Anna (Carbohydrate Polymer Technologies and Applications)
Row carpentry waste wood flour, constituted of poplar (∼60 %) and fir (∼30 %) biomass, was subjected for the first time to microwave-assisted deep eutectic solvent (DES) treatment, with the purposes of solubilizing lignin and hemicellulose, leaving cellulose as solid residue, thus performing a biorefinery. Several acidic (choline chloride/oxalic acid; choline chloride/citric acid; betaine hydrochloride/oxalic acid) and alkaline (urea/choline chloride; glycerol/K2CO3) DESs were employed under the same reaction conditions. Since the highest extraction yield was obtained by using choline chloride/oxalic acid DES, the use of the latter was investigated by varying some parameters (temperature, manner of microwave irradiation, addition of water) aiming at increasing the solubilization yield, which in fact in some cases reached satisfying values (60 %) under mild conditions. The solid residues (SRs) recovered after all treatments with all tested DESs were characterized by Thermogravimetric Analysis (TGA), Attenuated Total Reflectance-Fourier Tranform Infrared Spectroscopy, Solid-State NMR Spectroscopy, and titration of surface acid groups. All SRs were also ultrasonicated to produce cellulose nanoparticles which were in turn characterised by transmission electron microscopy (TEM) and dynamic light scattering (DLS) analyses. In addition, the solid residues recovered from acidic DESs were able to decontaminate water from organic pollutants, such as p-nitrophenol, by an adsorption process. Thus, the proposed DES treatment efficiently converted carpentry waste wood flour into a valuable biomaterial useful for environmental decontamination.